Impact of global value chains on tariffs and non-tariff measures in agriculture and food - Raimondi, Valentina; Pirui, Andreea; Swinnen, Johan; Olper, Alessandro (Elsevier, 2023)
We analyse whether global value chains (GVCs) reduce trade barriers in the agricultural and food sectors as they affect lobbying and government incentives. Political economy theory predicts that tariffs will be lower in countries integrated in GVCs and that the effect will be stronger outside regional trade agreements (RTAs). We use data from 1995 to 2015 from 160 countries on tariffs and non-tariff measures (NTMs) in the agri-food sector. Our evidence indicates that GVC integration, measured as domestic (foreign) value added in foreign (domestic) final goods, does affect trade policy. Stronger GVC integration is associated with lower tariffs, but mainly outside RTAs, and lower NTMs, both inside and outside RTAs.